Eikonal Blog

2012.03.14

Pretty little tables

Filed under: mathematics, number theory, puzzles — Tags: , — sandokan65 @ 14:59

Recently I have seen in an math forum this:

    Wonder #1

and just a few days later this one, too:

    Wonders 1-4

Pretty little tables, aren’t they? How could they be so regular? Can they be generalized somehow?

Answers are: yes, you will see, and yes.

Wonder #1

Let’s first take a look at the first table:

Table 1
  • 1 \times 8 + 1 = 9,
  • 12 \times 8 + 2 = 98,
  • 123 \times 8 + 3 = 987,
  • 1,234 \times 8 + 4 = 9,876,
  • 12,345 \times 8 + 5 = 98,765,
  • 123,456 \times 8 + 6 = 987,654,
  • 1,234,567 \times 8 + 7 = 9,876,543,
  • 12,345,678 \times 8 + 8 = 98,765,432,
  • 123,456,789 \times 8 + 9 = 987,654,321,

In order to understand it one has to work not with the specific numbers (digits), but with their abstract representations. For this, we will work with a number system of base B (\in {\Bbb N}), which in the orginal tables is B=10. Then we can rewrite several first members of the Table 1 as follows:

  • 1 \cdot B^0 \times (B-2) + 1 = (B-1) B^0,
  • (1 \cdot B^1 + 2 B^0) \times (B-2) + 2 = (B-1) B^1 + (B-2)B^0,
  • (1 \cdot B^2 + 2 B^1 + 3 B^0) \times (B-2) + 3 = (B-1)B^2 + (B-2)B^1 + (B-3)B^0,
  • etc

Ok, we see some regularity here. To proceed further, rewrite the n^{th} row of that table in the form a mathematical equation y_n :\equiv x_n \cdot \hbox{some number} + \hbox{some other number}, transforming the first beautifully looking number (x_n) into second beautifully looking number y_n.

Here the series \{x_n\} is:

  • x_1 = 1_B = 1\times B^0,
  • x_2 = 12_B = 1\times B^1 + 2 \times B^0,
  • x_3 = 123_B = 1\times B^2 + 2 \times B^1 + 3 \times B^0,
  • x_n = 123...n_B = 1\times B^{n-1} + 2 \times B^{n-2} + \cdots + n \times B^0 = \sum_{k=1}^n k B^{n-k}.
    A side note:
    Note that x_n =  \sum_{s=0}^{n-1} (n-s) B^s. It can be explicitly summarized as follows:

      x_ n = (n- B \partial_B) \sum_{s=0}^{n-1} B^s = (n-B\partial_B) \frac{B^n-1}{B-1} = \frac{B(B^n-1)-n(B-1)}{(B-1)^2}.

    For example, for B=10 that formula yields x_n = \frac{10(10^n-1)-9n}{81}: x_1 = 1, x_2 = 12, …, x_5 = 12345, etc.

Let’s go back to the main line of discussion.

Now we are interested in the following derivative series y_n :\equiv x_n \cdot (B-2) + n. The straightforward manipulation leads to the anticipated result:

    y_ n = B^n + \sum_{s=1}^{n-1} (s+1-n)B^s - n
    = (B-1)B^{n-1} + B^{n-1} + \sum_{s=1}^{n-2} (s+1-n)B^s - n
    = (B-1)B^{n-1} + (B-2) B^{n-2} + \sum_{s=1}^{n-3} (s+1-n)B^s - n

    \cdots

    = \sum_{r=1}^{m} (B-r)B^{n-r} + B^{n-m} + \sum_{s=1}^{n-m-1} (s+1-n)B^s - n

    \cdots

    = \sum_{r=1}^{n-2} (B-r)B^{n-r} + B^{2} + \sum_{s=1}^{1} (s+1-n)B^s - n
    = \sum_{r=1}^{n-2} (B-r)B^{n-r} + B^{2} + (2-n)B^1 - n
    = \sum_{r=1}^{n-1} (B-r)B^{n-r} + B^{1} - n
    = \sum_{r=1}^{n} (B-r)B^{n-r}.

i.e. y_n = (B-1)(B-2)...(B-n+2)(B-n+1)(B-n)_B. The initial pyramid of simple results holds for every base B.

Example: for B=5 we have x_n = \frac{5(5^n-1)-4n}{16}, so x_1 = \frac{5\cdot 4 - 4 \cdot 1}{16} = 1, x_2 = \frac{5\cdot 24 - 4 \cdot 2}{16} = 7_{10} = 12_5, etc. Then, for example y_2 = x_2 \cdot 3 + 2 = 7\cdot 3 + 2 = 21 + 2 = 23_{10} = 43_5.

Wonder #2

Let’s look at the Table 2:

Table 2
  • 1 \times 9 + 2 = 11,
  • 12 \times 9 + 3 = 111,
  • 123 \times 9 + 4 = 1,111,
  • 1,234 \times 9 + 5 = 11,111,
  • 12,345 \times 9 + 6 = 111,111,
  • 123,456 \times 9 + 7 = 1,111,111,
  • 1,234,567 \times 9 + 8 = 11,111,111,
  • 12,345,678 \times 9 + 9 = 111,111,111,
  • 123,456,789 \times 9 + 10 = 1,111,111,111,

Here the first (i.e. the independent) variable x_n is the exactly same as the one used for Table 1. The second (i.e. the dependent) variable z_n is new one, determined by defining equation:

    x_n = \sum_{s=0}^{n-1}(n-s)B^s,

Then, using steps similar to these used in analysis of the Table 1, we get:

    z_n :\equiv x_b \cdot (B-1) + (n+1) =
    = \sum_{s=0}^{n-1} (n-s) B^{s+1} - \sum_{s=0}^{n-1} (n-s) B^s + (n+1) =
    = \sum_{s=1}^{n} (n+1-s) B^{s} - \sum_{s=0}^{n-1} (n-s) B^s + (n+1) =
    = B^n + \sum_{s=1}^{n-1} (n+1-s - n +s) B^{s} - n + (n+1) =
    = B^n + \sum_{s=1}^{n-1} B^{s} +1 =
    = \sum_{s=0}^{n} B^{s} =
    = 1\cdots 1_B,

where there are (n+1) copies of digit 1.

Nice. Easy.

Wonder #3

Table 3
  • 9 \times 9 + 7 = 88,
  • 98 \times 9 + 6 = 888,
  • 987 \times 9 + 5 = 8,888,
  • 9,876 \times 9 + 4 = 88,888,
  • 98,765 \times 9 + 3 = 888,888,
  • 987,654 \times 9 + 2 = 8,888,888,
  • 9,876,543 \times 9 + 1 = 88,888,888,
  • 98,765,432 \times 9 + 0 = 888,888,888,

That series of relations has form v_n = u_n \cdot 9 + (8-n) where the dependent variable is
v_n = \underbrace{8\cdots8}_{n+1} in the normal decimal system (B=10).

For general basis B this generalizes to the:
v_n = u_n \cdot (B-1) + (B - n -2). Here the independent variable u_n is

    u_n = \sum_{k=1}^n (B-k) B^{n-k} =
    = \sum_{s=0}^{n-1} (B- n -s) B^s =
    = (B - n + B \partial_B) \sum_{s=0}^{n-1}B^s =
    = (B - n + B \partial_B)\frac{B^n-1}{B-1} =
    = \frac{B(B-2)(B^n-1)+n (B-1)}{(B-1)^2}.

Now

    v_ n :\equiv u_n (B-1) + (B-n-2) =
    = (B-1) B^n - \sum_{s=1}^{n-1} B^s - 2 =
    = (B-2) B^n + (B-1) B^{n-1} - \sum_{s=1}^{n-2} B^s - 2 =
    = (B-2) B^n + (B-2) B^{n-1} + (B-1)B^{n-2} - \sum_{s=1}^{n-3} B^s - 2 =

    \cdots

    = (B-2) B^n + \cdots + (B-2) B^{n-m+1} + (B-1)B^{n-m} - \sum_{s=1}^{n-m-1} B^s - 2 =

    \cdots

    = (B-2) B^n + \cdots + (B-2) B^{3} + (B-1)B^{2} - B^1 - 2 =
    = (B-2) B^n + \cdots + (B-2) B^{3} + (B-2)B^{2} + B^2 - B^1 - 2 =
    = (B-2) B^n + \cdots + (B-2) B^{2} + (B-1)B^{1} - 2 =
    = (B-2) B^n + \cdots + (B-2) B^{1} + B - 2 =
    = \sum_{r=0}^{n} (B-2) B^r.

For B=10 that covers all examples in the Table 3.

Note: Even more, we can add two more members to it, corresponding to n=9 and n=10:

  • u_9 = 987,654,321 corresponds to v_9 = x_9 \cdot 9 + (-1) = 8,888,888,888,
  • u_{10} = 9,876,543,210 corresponds to v_{10} = x_{10} \cdot 9 + (-2) = 88,888,888,888.

Also, the u_0=0 provides one more line, which is prepended to this more complete table 3:

Table 3*
  • 0 \times 9 + 8 = 8,
  • 9 \times 9 + 7 = 88,
  • 98 \times 9 + 6 = 888,
  • 987 \times 9 + 5 = 8,888,
  • 9,876 \times 9 + 4 = 88,888,
  • 98,765 \times 9 + 3 = 888,888,
  • 987,654 \times 9 + 2 = 8,888,888,
  • 9,876,543 \times 9 + 1 = 88,888,888,
  • 98,765,432 \times 9 + 0 = 888,888,888,
  • 987,654,321 \times 9 - 1  = 8,888,888,888,
  • 9,876,543,210 \times 9 - 2  = 88,888,888,888.

Wonder #4

Table 4
  • 1^2 = 1,
  • 11^2 = 121,
  • 111^2 = 12,321,
  • 1,111^2 = 1,234,321,
  • 11,111^2 = 123,454,321,
  • 111,111^2 = 1,2345,654,321,
  • 1,111,111^2 = 1,234,567,654,321,
  • 11,111,111^2 = 123,456,787,654,321,
  • 111,111,111^2 = 12,345,678,987,654,321.

Here the independent variable is

    p_n :\equiv 1\cdot B^{n} + 1\cdot B^{n-1} + \cdots + 1\cdot B^0 = \sum_{i=0}^n B^i = \frac{B^{n+1}-1}{B-1}.

The resulting variable is

    r_n :\equiv p_n^2 = \sum_{i=0}^n \sum_{j=0}^n B^{i+j} =
    = \sum_{k=0}^{2n} (\sum_{i=0}^n \sum_{j=0}^n \delta_{i+j,k}) B^k.

Now the sum in brackets can be transformed as follows:

    \sum_{i=0}^n \sum_{j=0}^n \delta_{i+j,k} = \sum_{i=0}^n  \Theta(0 \le  k-i \le n) =
    = \sum_{i=0}^n \Theta(k-n \le i \le k) =  \sum_{i=\hbox{max}(0,k-n)}^{\hbox{min}(n,k)} 1 =
    = \hbox{min}(n,k) - \hbox{max}(0,k-n) + 1 = *

which has three posible simplifications:

  • * = k - 0 + 1 = k + 1 for k < n,
  • * = n + 1 for k = n,
  • * = n - (k-n) + 1 = 2n - k + 1 for k > n.

So, now we can write the final form for r_n as following:

    r_n = \sum_{k=0}^{n-1} (k+1) B^k + (n+1) B^n + \sum_{k=n+1}^{2n} (2n-k+1) B^k =
    = 1\cdot B^0 + 2\cdot B^1 + 3\cdot B^2 + \cdots + (n+1) B^n + \cdots 2\cdot B^{2n-1} + 1\cdot B^{2n} =
    = 123\cdots(n+1)\cdots321_B.

That is it.


Note that one can get some regularities for degrees higher than 2. For example, for degree 3 one has:

    1^3 = 1
    11^3 = 1,331
    111^3 = 135,531

    1,111^3 = 13,577,531
    11,111^3 = 1,357,997,531
    111,111^3 = 135,79b,b97,531
    1,111,111^3 = 13,579,bdd,b97,531

    \cdots

    {\underbrace{1\cdots1}_{[B'/2]+1}}^3 = 1357\cdots B'B'\cdots 7531.

up to the last member (of that series) where the two central digits are the highest single-digit number B' allowed in the number system of base B (i.e. B'=B-2 if B is odd, and B'=B-1 if B is even).

Note: Here a = 10_{10}, b = 11_{10}, c = 12_{10}, d = 13_{10}, e = 14_{10}, f = 15_{10}, g = 16_{10}, h = 17_{10}, i = 18_{10}, etc.

For the degree 4 the similar pyramid/table is:

    1^4 = 1
    11^4 = 14,641
    111^4 = 1,48a,841

    1,111^4 = 1,48a,cec,841

    \cdots

Here one can also work some more (and I did not do that work yet) to establish which is the last member of that table (as a function of the base B), and what is the innermost digit in that last member.
This could be a homework for you. 🙂

For the degree 5:

    1^5 = 1
    11^5 = 15885
    111^5 = 15ciic51

    \cdots


Similar here: More simple math wonders – https://eikonal.wordpress.com/2012/03/14/more-simple-math-wonders/ | Mental calculation of cube root of a six-digit number – https://eikonal.wordpress.com/2010/01/14/mental-calculation-of-cube-root-of-a-two-digit-number/ | Squares with just two different decimal digits – https://eikonal.wordpress.com/2010/01/05/squares-with-just-two-different-decimal-digits/ | Number theory finite concidental sums – https://eikonal.wordpress.com/2010/01/05/number-theory-finite-considental-sums/

Advertisements

3 Comments »

  1. […] T1277 Similar here: More simple math wonders – https://eikonal.wordpress.com/2012/03/14/more-simple-math-wonders/ | Mental calculation of cube root of a six-digit number – […]

    Like

    Pingback by Number theory finite concidental sums « Eikonal Blog — 2012.03.14 @ 15:30

  2. […] T1277 Similar here: More simple math wonders – https://eikonal.wordpress.com/2012/03/14/more-simple-math-wonders/ | Mental calculation of cube root of a six-digit number – […]

    Like

    Pingback by Squares with just two different decimal digits « Eikonal Blog — 2012.03.14 @ 15:32

  3. […] More simple math wonders […]

    Like

    Pingback by Mental calculation of cube root of a six-digit number « Eikonal Blog — 2012.03.14 @ 15:32


RSS feed for comments on this post. TrackBack URI

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s

March 2012
M T W T F S S
« Feb   Apr »
 1234
567891011
12131415161718
19202122232425
262728293031  
  • Categories

  • Archives

  • Join 36 other followers

  • Recent Posts

  • atheism awk bash bookmarklets books climate change cloud computing critical thinking crypto cygwin evolution excel Exponential splittings facebook facebook dirty tricks Facebook privacy firefox fitness Gamma function health infosec Integral Transforms JavaScript knowledge management language acquisition LaTeX latin language learning language learning languages linguistics linux martial arts math Matrix exponentials MD5 meme memetics Moore-Penrose inverse music nessus networking nmap opression password 7 password cracking patents Penetration testing Perl physics powershell privacy productivity regular expressions religion scripting security tools sed shell skills Snopes software patents SourceForge ssh SSL SSl certificates sums surveilance text processing tracking transcendental numbers transformers TSA unix WikiLeaks workout
  • Blog at WordPress.com.